Scripts elegant lettering from design's golden age - Heller, Steven 1950-; Fili, Louise 1951- (Thames & Hudson, 2011)
"Seen in everything from wedding invitations and birth announcements to advertisements, menus, street signs, and diplomas, script typefaces impart elegance and sophistication to a broad variety of texts. Scripts never go out of style, and the hundreds of inventive examples here, many found in obscure sources from across Europe and America, are sure to inspire today's designers"--Back cover
Introduction -- French : scriptes -- British : scripts -- German : der Schrift -- Italian : il corsivo -- American : scripts -- Further reading
Includes bibliographical references (p. 350)
Keywords: Geschichte 1800-1950; Lettering; Calligraphy; Alphabet books; Typografie